Ukhuwwah al-Islamiyyah as the Basic Foundation of Islamic Moderation: Study of Abdullah bin Nuh's Works - Ardi, M.; Abdullah, F.; Cholil, A. (Universiti Sains Islam Malaysia, 2024)
Basically, Allah creates the all human being on the earth to know each other and to create love between them without any differences of religion, tribes, cults, and others. Islam as the universal religion teaches its adherents to avoid the violence between Muslim brothers as well as non-Muslim; therefore, Islam accentuates dialogue to realize the tolerance and co-existence in unity and diversity of life. However, nowadays, the values and ethic of Islam on Ukuhuwah Islamiyah have left by the majority of Muslims. The difference on the framework of viewing concept of Islam is occurred crucial controversy among Muslim brothers in understanding of Islam its self. As the result, among Muslims, they judge infidel to fellow Muslim and destroy each other, even though, they still believe to one God of Allah and His messenger, and also one Qibla of Ka’ba in Macca. Finally, Islam is stagnant in its realizing of its mission and vision in development of human life. This study use analytical descriptive mathode in order to relevantize Abdullah bin Nuh’s thought in current issues of Islamic thought. Abdullah bin Nuh is one of Muslim scholar that has great concern and deep attention to regrow of brotherhood among Muslims with the concept of Ukuhwah Islamiyyah. According to him, Ukhuwwah Islamiyyah applies to the whole of Muslim world without any distinction of countries, sects, tribes, as long as they still on one of Shahadah of Allah and His messenger. The concept of Abdullah bin Nuh on Ukhuwwah Islamiyyah is relevance to Muslim problematical today, when the majority of Muslim countries collapse with one issue of sects, for example, the controversy of Sunni and Shia. Abdullah bin Nuh devoted throughout his life to avoid the issues of furu’iyyah and controversy between Sunni and Shia. Moreover, he always cooperates with Iran scholar in term of academic research to encounter modern ideologies.